Adaptive hybrid virtual inertia controller for PMSG-based wind turbine based on fuzzy logic control - Mohamed Hosny; Mostafa I. Marei; Ahmed M.I. Mohamad (Scientific Reports)
Abstract The integration of renewable energy sources into microgrids presents some challenges due to the decreased system overall inertia associated with the presence of converter -based sources. To overcome this issue and to enhance the system inertia, various concepts for virtual inertial control have been proposed in the literature. However, the concept of improving the system frequency through wind turbines has gained widespread acceptance. Several frequency support techniques have been proposed recently. However, conventional virtual inertia controllers may not satisfy the performance requirements in terms of frequency nadir and rate of change of frequency (ROCOF) over a wide range of microgrid operating conditions. This paper proposes a hybrid adaptive virtual inertia control strategy based on Fuzzy logic. The hybrid strategy integrates kinetic energy based virtual inertia control and virtual capacitance control schemes. The gains of both KE based virtual inertia control loop and virtual capacitance control loop are adapted simultaneously to enhance frequency support of low inertia microgrid under wide range of renewable energy sources (RES) disturbances and load changes. Different case studies are simulated on MATLAB/ Simulink to evaluate the dynamic performance of the proposed adaptive hybrid virtual inertia strategy under different conditions.